2022
DOI: 10.3389/fnagi.2022.919143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of brain microstructure alterations on diffusion kurtosis imaging among Alzheimer’s disease, mild cognitive impairment, and cognitively normal individuals

Abstract: ObjectiveOur study aimed to explore the differences in brain microstructure in patients with Alzheimer’s disease (AD) and with mild cognitive impairment (MCI) and in individuals with normal cognition using diffusion kurtosis imaging (DKI) to identify a potential non-invasive biomarker of AD.Materials and methodsA total of 61 subjects were included in our study, including 20 subjects diagnosed with AD, 21 patients diagnosed with amnestic MCI, and 20 cognitively normal individuals. We acquired magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that MK and K radial exhibited a greater extent and degree of SIVD–AD differences than K axial within the WM 12 and thalamus 8 . Another report has shown that radial metrics could possess higher sensitivity in detecting AD, mild cognitive impairment, and cognitively normal individuals 13 . As consistent with previous reports, the radial metrics could provide higher sensitivity in detecting the microstructural alterations especially in SIVD and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MK and K radial exhibited a greater extent and degree of SIVD–AD differences than K axial within the WM 12 and thalamus 8 . Another report has shown that radial metrics could possess higher sensitivity in detecting AD, mild cognitive impairment, and cognitively normal individuals 13 . As consistent with previous reports, the radial metrics could provide higher sensitivity in detecting the microstructural alterations especially in SIVD and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging is widely used to assist with the diagnosis and neurodevelopmental prediction of infants with HIE. Studies have compared DKI-related parameters with the indicators provided by DTI, including studies involving clinical research pathologies and applications, such as the developing brain (Grinberg et al, 2017 ; Shi et al, 2019 ), glioma (Raab et al, 2010 ; Van Cauter et al, 2012 ), epilepsy (Guo et al, 2022 ), stroke (Hui et al, 2012b ; Umesh Rudrapatna et al, 2014 ), traumatic brain injury (Wang et al, 2018 ), multiple sclerosis (Raz et al, 2013 ), autism (McKenna et al, 2020 ), Alzheimer's disease (Chu et al, 2022 ), schizophrenia (McKenna et al, 2019 ), Huntington's chorea (Blockx et al, 2012 ), and Parkinson's disease (Bai et al, 2021 ). However, studies on the application of DKI to HIE are relatively rare.…”
Section: Introductionmentioning
confidence: 99%